Pengembangan konseling behavioral teknik modeling untuk meningkatkan self regulated learning siswa - Latsiar Simanjuntak; Luh Putu Sri Lestari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to develop a behavioral counseling guidebook using the modeling method to improve high school students' self-regulated learning. This handbook is a guide for counseling teachers in conducting counseling tutorial services in schools. The development procedure in this research explores the 4D development model proposed by Thiagarajan, (1974). Evaluation of the acceptability of this guidebook was assessed by 5 judges in the field of counseling tutorials. The evaluation instrument used consisted of 22 statement items referring to the acceptability of the guidebook. Acceptability analysis uses the formulation of the calculation of the Content Validity Ratio (CVR) from Lawshe, (1975). The results show content validity (CVI) of 1 which means very good or special. This shows that the modeling technique behavioral counseling guidebook that was developed already meets the acceptance criteria. Trial to involve 3 students and in this research using a single subject design method with A-B-A design and the method of analyzing the data using graphic analysis. Variable measurement using percentage (%). In the effectiveness test, the results of baseline-1(A) self-regulated learning for the first student were (54.16%), the second student was (54.16%), the third student was (62.05%). In the intervention condition (B) self regulated learning the first student is at (61.66% - 90.41%), the second student is at (63.33% - 90.83%), the third student is at (66.66% - 98.33%). In the baseline-2 (A) condition, the first student's self regulated learning was at (95%), the second student was at (95.83%), the third student was at (99.58%). It can be concluded that the development of a behavioral counseling guidebook with modeling techniques is effective for increasing the self-regulated learning of high school students.